Finance and Development, March 1965. (Finance and Development; Finance and Development, 1965)
This paper examines the importance of national planning for economic development of a country. The paper highlights that when World War II began, Soviet Russia was the only country engaged in systematic development planning, and then only since 1929, when its First Five-Year Plan was approved. At the end of the War, Asian countries that either had, or were about to, become independent, embraced planning to a much greater extent than countries in any other region.